The Effectiveness of Social Communication in Creating a Conducive Atmosphere in Penajam Paser North District through Facilitation P4GN & PN - Sardo Jan Warisman Saragih; Yusmanizar Yusmanizar; Andi Vita Sukmarini (Borong Newinera Publisher, 2024)
This research aims to determine the effectiveness of social communication in creating a conducive atmosphere in North Penajam Paser Regency through facilities for the Prevention, Eradication, Abuse and Illicit Trafficking of Narcotics and Narcotics Precursors (P4GN & PN). When this research was carried out, he met directly with the Head of the National Unity and Politics Agency through the Head of the Development of Iwasbang, Community Organizations and Economic, Social and Cultural Resilience. Apart from that, conducting interviews with several related sources such as the Health Service, PPU District Narcotics Agency (BNK), PPU District Prosecutor's Office, PPU 0913 Military District Command, PPU Cq Resort Police. Narcotics Unit, Bangun Mulya Village, Waru District. The negative impact resulting from drug abuse is very large, not only does it have an impact on physical health problems, but it also has an impact on psychological/mental health problems. Drug prevention and control efforts can be carried out in preventive or repressive ways. The existence of the North Penajam Paser Regency National Narcotics Agency is expected to be able to assess and suppress the still high level of drug abuse to the extent of the effectiveness of social communication in creating a conducive atmosphere in North Penajam Paser Regency through facilitating the prevention, eradication, abuse and illicit trafficking of narcotics and narcotics precursors (P4GN & PN).